PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA GUNA MENINGKATKAN HASIL BELAJAR IPA KELAS 5 SD - Budi Prastowo; Slameto .; Elvira Hoesein Radia (Universitas Negeri Medan, 2018)
Abstract: Application Of Inkuiri Learning Model Assisted To Improve Media Learning Learning Results 5th grade SD. The purpose of this study is to describe the application of inquiry model of media-aided learning to improve the learning outcomes of science students 5th grade elementary school. The subjects of the study were 5th graders, which were 18 students. Classroom action research was conducted in two cycles by applying the media-aided inquiry model. Data analysis techniques applied are guidelines for observation and test of learning outcome, in the form of multiple choice test and essay. The result of the research shows that the application of inquiry model of media-assisted learning can improve the students' learning achievement. Cycle I average test scores 79 with completeness reached 67% and the average test II cycle 84 with completeness reached 92%, so research shows that the model of inquiry learning media can help improve the completeness of student learning outcomes.Keywords: Inquiry learning model, Media, Learning outcomesAbstrak : Penerapan Model Pembelajaran Inkuiri Berbantuan Media Guna Meningkatkan Hasil Belajar IPA Kelas 5 SD. Tujuan penelitian ini adalah medeskripsikan penerapan model pembelajaran inkuiri berbantuan media untuk meningkatkan hasil belajar IPA siswa kelas 5 SD. Subjek penelitian adalah siswa kelas 5 yang berjumlah 18 orang. Penelitian tindakan kelas dilaksanakan dalam dua siklus dengan menerapkan model pembelajaran inkuiri berbantuan media. Teknik analisis data yang diterapkan merupakan pedoman observasi dan tes hasil belajar, berbentuk tes pilihan ganda dan esai. Hasil penelitian menunjukan penerapan model pembelajaran inkuiri berbantuan media dapat meningkatkan ketuntasan hasil belajar siswa. Siklus I rata-rata nilai tes 79 dengan ketuntasan mencapai 67% dan siklus II rata-rata tes 84 dengan ketuntasan mencapai 92%, sehingga penelitian menunjukan bahwa model pembelajaran inkuiri berbantuan media dapat meningkatkan ketuntasan hasil belajar siswa.Kata Kunci : Model Pembelajaran Inkuiri, Media, Hasil Belajar